2023
DOI: 10.4300/jgme-d-22-00497.1
|View full text |Cite
|
Sign up to set email alerts
|

Educational Outcomes of Diversity Curricula in Graduate Medical Education

Abstract: Background Education is an important step toward achieving equity in health care. However, there is little published literature examining the educational outcomes of curricula for resident physicians focused on diversity, equity, and inclusion (DEI). Objective Our objective was to review the literature to assess the outcomes of curricula for resident physicians of all specialties focused on DEI in medical education and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…There is some evidence to suggest that integration of DEI training into continued medical education modules may improve provider skills in providing culturally competent services and patient satisfaction [ 65 , 66 ]. Previous studies have also found that incorporating DEI material into graduate medical education was feasible and well received [ 67 ]. Co-engagement with providers may also involve establishing regular forums or workshops to discuss case studies and share insights on reducing disparities.…”
Section: Resultsmentioning
confidence: 99%
“…There is some evidence to suggest that integration of DEI training into continued medical education modules may improve provider skills in providing culturally competent services and patient satisfaction [ 65 , 66 ]. Previous studies have also found that incorporating DEI material into graduate medical education was feasible and well received [ 67 ]. Co-engagement with providers may also involve establishing regular forums or workshops to discuss case studies and share insights on reducing disparities.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is a significant improvement in the communication skills of students, and this becomes quite evident in improved trust and better doctor-patient relationships (9). As students with diverse perspectives learn together, there is a significant improvement in their problemsolving skills and they can come up with more comprehensive and innovative solutions to complex medical challenges (10). As the cohort of medical students are from varied demographics and geographical regions, it becomes easier for them to relate with the broad range of patients from similar settings and accordingly improve patient outcomes (9,10).…”
Section: Medical Educationmentioning
confidence: 99%
“…As students with diverse perspectives learn together, there is a significant improvement in their problemsolving skills and they can come up with more comprehensive and innovative solutions to complex medical challenges (10). As the cohort of medical students are from varied demographics and geographical regions, it becomes easier for them to relate with the broad range of patients from similar settings and accordingly improve patient outcomes (9,10). As students are exposed to a diverse range of patients, their experiences, and the challenges encountered by them, it fosters empathy among medical students (11).…”
Section: Medical Educationmentioning
confidence: 99%
See 1 more Smart Citation